Internalization of Islamic Social Etiquette Values in Forming Religious Social Ethics of Students at SMP 45 Gerbo - Faqih, Moch. Abdulloh; Yusuf, Achmad; Yusuf, Wiwin Fachrudin (Yayasan Rahmat Islamiyah, 2025)
This study aims to describe the internalization of Islamic social etiquette values in forming students' social religious ethics at SMP 45 Gerbo. The background of this study is based on the phenomenon of declining social ethical attitudes among adolescents, so that systematic efforts are needed through strengthening Islamic values. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The data sources were obtained from Islamic Religious Education teachers, students, and various supporting documents at SMP 45 Gerbo. The results of the study indicate that the internalization of Islamic social etiquette values at SMP 45 Gerbo is reflected through the values of obedience in worship, discipline, honesty, respect for teachers and parents, brotherhood and cooperation, tolerance, and guarding the tongue. The internalization strategies used include role models, habituation, giving advice, and implementing educative punishments (tsawab). Internalization of these values strengthens the formation of students' social religious ethics in everyday life in the school environment.